Acousmatic Foley: Staging sound-fiction. Issue 3 (11th November 2016) - Pinheiro, Sara
Abstract : This article proposes a narrative theory thought in terms that are specific to sound practice. It addresses two different fields – Acousmatic Music and Foley Art – as a possibility of understanding sound narration and conceptualising it around the idea of fiction. To this end, it begins from the concepts of sound-motif, sound-prop and sound-actors, in order to propose a dramaturgic practice specific to sound terms. The theory of sound dramaturgy acquires a practical outline by making use of multichannel constellations as a composition strategy, with specific loudspeaker arrangements. The theory advocates loudspeakers as the mediators of the experience and the stage as part of the audience's assembly. This translates into a practice of staging sound fiction, which focuses on formulating a conjecture based on formal and factual structures, allowing for a direct relationship between the listener and the listening, between the sounds and their fictional location.